Порівняльна характеристика складу і розподілу екобіоморфа степового і техногенного екотопів - Чайка, Микола; Chaika, Mykola; Мицик, Олександр; Chaika, Oleksandr (ООО «Содружество», 2019)
У статті зроблена спроба виявити особливості різноманітності складу екобіоморфа рослинних по- Кров Тирловской степової цілини і породного відвалу шахти №10, міста Донецька, і дано порівняльний аналіз Біоморфологічні і еколого-ценотического спектрів населяють видів. В роботі представлені дані видового складу рослинних угруповань, дано аналіз флористичного багатства, Біоморфологічні і еколого-ценотичних структурі фітоценозів. Визначено поняття: ступінь представленості екобіоморфа, питомої ємності складу екобіоморфа, розподіл складу екобіомрф, локалітет екобіоморфа. The attempt to identify the diversity peculiarities of the composition of ecobiomorph vegetation of Tyrlovsk steppe virgin soil and the waste dump of mine № 10 in Donetsk was made and the comparative analysis of biomorphological, ecological and coenotic specters of the inhabiting species is given in the article. The paper presents the data of the species composition of the plant communities, the analysis of floristic wealth, biomorphological, ecological and coenotic structure of phytocenosis is given. The following concepts are defined: the degree of ecobiomorph representation, the specific capacity of ecobiomorph composition, the ecobiomorph composition distribution, the ecobiomorph locality.
The comparative characteristics of the composition and disrtibution of ecobiomorphs of the steppe and technogenic ecotops
Keywords: рослинний покрив; vegetation cover; видовий склад; species composition; флористичне багатство; floral wealth; биоморфа; biomorph; екоморфа; ectomorph